2022
DOI: 10.3390/jpm12060860
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mapping the Effects of Chronic Aerobic Exercise in the Rat Brain Using FDG PET

Abstract: Exercise is a key component to health and wellness and is thought to play an important role in brain activity. Changes in brain activity after exercise have been observed through various neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) and positron emission tomography (PET). The precise impact of exercise on brain glucose metabolism (BGluM) is still unclear; however, results from PET studies seem to indicate an increase in regional metabolism in areas related to cognition and memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…However, it was not found that the above four regions were related to the three sub-functions of EF. The putamen, caudate, and thalamus are the most concentrated parts of motor conduction and integration coordination, and they play an important role in CRF but are less related to EF [ 60 ]. The parahippocampal region may be the only one of four regions associated with EF.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not found that the above four regions were related to the three sub-functions of EF. The putamen, caudate, and thalamus are the most concentrated parts of motor conduction and integration coordination, and they play an important role in CRF but are less related to EF [ 60 ]. The parahippocampal region may be the only one of four regions associated with EF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the group size seems small, but several studies used similar number of animals [ 37 , 42 , 67 ], and in both series of experiments the saline-treated control and Wisket animals showed similar values, suggesting a good reliability of the obtained parameters.…”
Section: Discussionmentioning
confidence: 94%
“…Data collected in vivo to support these findings are still scarce and sought after. A PET study using [ 18 F]FDG and static image acquisition to determine the effects of regular aerobic exercise on cerebral glucose metabolism in different parts of the brain was conducted on healthy young-adult fasted rats after six weeks of involuntary treadmill running, revealing increased metabolism in brain regions associated with auditory processing, memory, motor function, and motivated behavior [ 33 ]. These findings showcase the effect that exercise has on the brain and underline the need for further research with more sophisticated methods to discover the underlying mechanisms.…”
Section: Expected Resultsmentioning
confidence: 99%